HLA-alleles class I and II associated with genetic susceptibility to neuromyelitis optica in Brazilian patients - Cláudia Suemi Kamoi Kay; Rosana Herminia Scola; Raquel Cristina Arndt; Paulo José Lorenzoni; Lineu Cesar Werneck (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: To study the genetic susceptibility to neuromyelitis optica (NMO) as well as the relationship between HLA genotypes and susceptibility to the disease in the southern Brazilian population. Methods: We analyzed patients with NMO, who met criteria for Wingerchuk's diagnosis of NMO, with detected serum anti-AQP4-IgG antibody. The HLA genotyping was performed by high-resolution techniques (Sanger sequencing) in patients and controls. The HLA genotypes were statistically compared with a paired control population. Results: The HLA genotyping revealed the diversity of the southern Brazilian population whose HLA profile resembled European and Asian populations. Some alleles had statistical correlations with a positive association (increased susceptibility) with NMO, particularly the HLA-DRB1*04:05 and *16:02. Conclusions: In our study, the HLA genotype was different to that previously reported for other Brazilian populations. Although our study had a small cohort, HLA genotypes were associated with increased susceptibility to NMO for HLA-DRB1*04:05 and *16:02. The alleles of HLA class I HLA-A*02:08 and *30:09, HLA-B*08:04 and *35:04 showed an association before the Bonferroni correction.